PER CAPITA FUNDING INSTRUMENT FOR SUBSIDIZING INCLUSIVE EDUCATION IN KAZAKHSTAN - Shaidarova, Karina; Nurbekova, Elmira; Baishan, Almas (Nazarbayev University Graduate School of Public Policy, 2024)
This study critically evaluates Kazakhstan's per capita funding instrument for inclusive education, designed to allocate funds based on student enrollment to support equitable access for students with special needs. Introduced in 2018 as a pilot program, the instrument has since expanded nationwide; however, gaps remain between policy goals and practice, with challenges around funding adequacy, inconsistent implementation, and varied practitioner perspectives. Using a mixed-methods approach, including surveys and interviews with educational staff, this research identifies critical issues, such as insufficient resources, lack of standardization across regions, and disparities in tutor workloads. Findings reveal an average effectiveness rating of 6.4 out of 10, underscoring areas for improvement. Administrative staff reported greater challenges with operational implementation compared to school management, highlighting a need for unified training. Major recommendations include separating fixed operational costs from per capita funds, providing differentiated pay for tutors based on workload, and establishing robust monitoring mechanisms. These adjustments aim to improve the instrument’s transparency and accountability, ensuring that funds are used effectively to meet inclusive education goals. Overall, the study emphasizes that while the per capita funding instrument holds potential, substantive reforms are required to align it with Kazakhstan’s goals for inclusive education. Implementing these recommendations could bridge policy-practice gaps, fostering a more equitable and effective system for inclusive education funding.
Keywords: Type of access: Open